Disconnect Between Planning and Practice? A Critical Evaluation of Urban Spatial Policies in South Sulawesi - Lira, M. Adnan (Manunggal Halim Jaya, 2025)
The rapid growth of Makassar and other urban areas in South Sulawesi has posed significant challenges for spatial planning. This study assesses the effectiveness of spatial planning policies in supporting urban development in the province. Using a quantitative survey approach complemented by qualitative secondary data, the research employs multiple regression analysis via SAS software and descriptive analysis for secondary sources. Findings reveal that spatial planning strategies are not yet harmonized across provincial and district/city levels, limiting their effectiveness in guiding urban growth. This lack of alignment is attributed to several factors: weak policy coordination (legal substance), inadequate data and infrastructure, limited inter-agency collaboration, and the complex, multi-sectoral governance of urban land (legal structure). To address these issues, the study proposes the creation of an integrated institution with complete authority over land use management to monitor, evaluate, and enforce spatial policies. Additionally, the authorities must revise spatial planning regulations, strengthen institutional capacities, and enhance public awareness through education and outreach targeting communities and developers.